Perencanaan Sistem Order Dalam Pelayanan Melalui Aplikasi Delivery Order Di Roti’O - Dwi Darmawan, Dimas; Rivalzi, Rudi; Pertiwi Hari Sandi, Santi; Epty Hidayaty, Dwi (Jurnal Etnik: Ekonomi-Teknik, 2023)
Roti'O is known as a franchise company with its flagship product, the coffee bun. Roti'O's first outlet was established on May 23, 2012 at Kota Station, West Jakarta. Roti'O is a brand under PT. Sebastian Citra Indonesia. This study aims to determine the planning of the order system in service through the delivery order application at Roti'o. The method used is descriptive. Descriptive is a research method that describes the characteristics of the population or phenomenon studied. Therefore, the main focus of this research method is to explain the research object. So that is in accordance with what events or phenomena are happening. In general, the results of this study Roti'O still do not have a Roti'O delivery application that can make it easier for consumers. Currently, the development is so rapid, many social media are used to facilitate quick access to social media. We hope that this online order delivery will make it easier for customers to shop and save time busy with every other work in daily life